12 Basic Values of Peace Generation for the Young Generation in Preventing Social Conflicts - Laila Nihayati (PT Publikasiku Academic Solution, 2023)
Social conflict is a problem that often occurs in society. To prevent social conflicts, it is necessary to adopt the values of peace in everyday life. Peace Generation has identified 12 basic peace values that can be adopted by the younger generation in preventing social conflicts. This study aims to identify the values of peace adopted by the younger generation and how these values can be applied in everyday life to prevent social conflicts. The research method used is a survey through questionnaires distributed to the younger generation. The results showed that the younger generation realized the importance of peace values in preventing social conflicts. All the basic values of peace identified by the Peace Generation are adopted by the younger generation. However, there were differences in the level of adherence to these values between respondents. The results of this study show that the younger generation understands the values of peace that are important in preventing social conflicts. Therefore, policymakers and educators need to strengthen peace values education in education curricula and activities outside schools to strengthen young people's adherence to these values. Thus, it is hoped that social conflicts can be avoided and peace can be achieved in society.